Analisis Implementasi Kurikulum Merdeka Belajar di MIS At-Taqwa Wawonduru - Muh. Irfan; Nur Islamiati; Ratnah Ratnah (Journal on Education, 2023)
The purpose of this study was to analyze how the implementation of the independent learning curriculum at the Mis At-Taqwa school was used. This study used two approaches, namely qualitative and quantitative with a descriptive type. The place of this research is at the Mis At-Taqwa school with a total of 16 teachers as subjects. Data collection techniques using interviews and questionnaires with a Likert Scale type. The results showed that: 1) Aspects of Knowledge and Understanding of the Independent Learning Curriculum got a percentage value of 87% in the good category; 2) The readiness aspect in implementing the independent learning curriculum obtained 82.5% in the good category; 3) Aspects of Implementation of Independent Learning Learning with a percentage of 64.06% is quite good; and 4) Aspects of Obstacles and Solutions to the Implementation of the Independent Learning Curriculum, obtaining a percentage value of 70.62% in the fairly good category.